2021
DOI: 10.1073/pnas.2100686118
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeler Arid1a regulates subplate neuron identity and wiring of cortical connectivity

Abstract: Loss-of-function mutations in chromatin remodeler gene ARID1A are a cause of Coffin-Siris syndrome, a developmental disorder characterized by dysgenesis of corpus callosum. Here, we characterize Arid1a function during cortical development and find unexpectedly selective roles for Arid1a in subplate neurons (SPNs). SPNs, strategically positioned at the interface of cortical gray and white matter, orchestrate multiple developmental processes indispensable for neural circuit wiring. We find that pancortical delet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…For transcription factors to access DNA information, histone proteins must first be repositioned or evicted from the chromosomes, a function that is performed by ATP-dependent chromatin remodeling complexes such as BAF (BRG1/BRM-associated factor) (mammalian SWI/SNF) complexes, which are composed of 14 to 16 individual protein subunits in human cells ( 22 ). These complexes control multiple cellular processes such as cell proliferation, transcriptional activation, differentiation, and chromatin remodeling ( 23 25 ). However, chromatin remodeling complexes regulating gametogenesis have not been identified in P. falciparum although, Plasmodium gametocytogenesis and gametogenesis likely requires chromatin remodeling to regulate expression of specific genes.…”
Section: Introductionmentioning
confidence: 99%
“…For transcription factors to access DNA information, histone proteins must first be repositioned or evicted from the chromosomes, a function that is performed by ATP-dependent chromatin remodeling complexes such as BAF (BRG1/BRM-associated factor) (mammalian SWI/SNF) complexes, which are composed of 14 to 16 individual protein subunits in human cells ( 22 ). These complexes control multiple cellular processes such as cell proliferation, transcriptional activation, differentiation, and chromatin remodeling ( 23 25 ). However, chromatin remodeling complexes regulating gametogenesis have not been identified in P. falciparum although, Plasmodium gametocytogenesis and gametogenesis likely requires chromatin remodeling to regulate expression of specific genes.…”
Section: Introductionmentioning
confidence: 99%
“…Sanger sequencing of the affected fetus confirmed the presence of the frameshift, and its absence in both parents. ARID1A encodes a member of the SWItch/Sucrose Non-Fermenting (SWI/SNF) complex, mediating processes such as the regulation of gene expression, cellular proliferation, apoptosis, differentiation, and the repair of genetic material [ 47 ]. Recently, a conditional Arid1a KO mouse model showed that pancortical Arid1a deletion led to extensive mistargeting of intracortical axons and corpus callosum agenesis [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…ARID1A encodes a member of the SWItch/Sucrose Non-Fermenting (SWI/SNF) complex, mediating processes such as the regulation of gene expression, cellular proliferation, apoptosis, differentiation, and the repair of genetic material [ 47 ]. Recently, a conditional Arid1a KO mouse model showed that pancortical Arid1a deletion led to extensive mistargeting of intracortical axons and corpus callosum agenesis [ 47 ]. Human mutations in this gene are associated with Coffin–Siris syndrome (CSS), a disorder rarely linked to hydrocephalus.…”
Section: Resultsmentioning
confidence: 99%
“…The pathfinding of cortical axons is dependent on correct specification of layer identities ( 41 ), and axon guidance mediated by SP neurons ( 53 , 74 , 75 ). We thus analyzed cortical axon tracts ( Fig.…”
Section: Resultsmentioning
confidence: 99%